A New Prognostic Score Supporting Treatment Allocation for Multimodality Therapy for Malignant Pleural Mesothelioma: A Review of 12 Years' Experience. Issue 11 (November 2015) - Opitz, Isabelle; Friess, Martina; Kestenholz, Peter; Schneiter, Didier; Frauenfelder, Thomas; Nguyen-Kim, Thi Dan Linh; Seifert, Burkhardt; Hoda, Mir Alireza; Klepetko, Walter; Stahel, Rolf A.; Weder, Walter
Abstract : Introduction: Treatment of malignant pleural mesothelioma (MPM) remains a clinical challenge. The aim of this study was to identify selection factors for allocation of MPM patients to multimodal therapy based on survival data from 12 years of experience. Methods: Eligible patients had MPM of all histological subtypes with clinical stage T1–3 N0–2 M0. Induction chemotherapy consisted of cisplatin/gemcitabine (cis/gem) or cisplatin/pemetrexed (cis/pem), followed by extrapleural pneumonectomy (EPP). Multivariate analysis was performed to assess independent prognosticators for overall survival (OS). A Multimodality Prognostic Score was developed based on clinical variables available before surgery. Results: From May 1999 to August 2011, 186 MPM patients were intended to be treated with induction chemotherapy followed by EPP. Hematologic toxicity was significantly less frequent after cis/pem compared to cis/gem, but there was no difference in response or OS between the regimens. One hundred and twenty-eight patients underwent EPP with a 30-day mortality of 4.7%. Fifty-two percent of the patients received adjuvant radiotherapy. The median OS of patients undergoing EPP was significantly longer with 22 months (95% confidence interval: 20–24) when compared to 11 months (9–12) for patients treated without EPP. A prognostic score was defined considering tumor volume, histology, C-reactive protein level, and response to chemotherapy that identified patient groups not benefitting from multimodality treatment which was confirmed in an independent cohort. Conclusion: Patients receiving induction chemotherapy followed by EPP for MPM of all histological subtypes and irrespective of nodal status showed a median survival of 22 months. A prognostic score is proposed to help patient allocation for surgery after validation in an independent cohort.